Intraductal Papillary Mucinous Neoplasm (IPMN) and Chronic Pancreatitis: Overlapping Pathological Entities? Two Case Reports - Petrou, Athanasios; Papalambros, Alexandros; Brennan, Nicholas; Prassas, Evangelos; Margariti, Thoedora; Bramis, Konstadinos; Rozemberg, Theofilos; Papalambros, Efstathios (JOP. Journal of the Pancreas, 2011)
Context Intraductal papillary mucinous neoplasms (IPMNs) are a recently classified pancreatic neoplasm with an increasing incidence. IPMN is often misdiagnosed as chronic pancreatitis because of symptoms of relapsing abdominal pain, pancreatitis, and steatorrhea and imaging findings of a dilated pancreatic duct of cystic lesions that are frequently confused with pseudocysts. Early recognition of IPMN allows for prompt surgical resection before malignant transformation. Case reports We report two cases of patients with long histories of chronic pancreatitis (more than 15 years) that went on to develop IPMN. Both patients presented with symptoms of abdominal pain, nausea, steatorrhoea and eventually weight loss. Biochemical and radiological findings were suggestive of chronic pancreatitis although no clear causes for this were identified. Both patients were followed up with multiple repeat scans with no reported sinister findings. Many years after the initial diagnosis of chronic pancreatitis, radiological investigations identified pathological changes suggestive of neoplastic development and histology confirmed IPMN. Conclusions The cases demonstrate the ongoing challenges in diagnosing and managing IPMN effectively; highlights the important aspects of epidemiology in differentiating chronic pancreatitis and IPMN; continues the discussion surrounding the relationship between IPMN and chronic pancreatitis. Image: Intraoperative findings of the Whipple surgical specimen.